2013
DOI: 10.1002/jmri.23934
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of liver and pancreas on late hepatic arterial phase Imaging: Quantitative comparison among multiple gadolinium-based contrast agents at 1.5 tesla MRI

Abstract: Our study describes % enhancement of liver and pancreas using various GBCAs. The data may provide reference material on relaxation properties of GBCAs in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The relatively low specific organ percent enhancement compared to other studies (1,25,26) possibly reflects the hybrid nature of the final images combining data across multiple phases: pre-contrast, immediate post-injection, hepatic arterial, and early portal venous phases, which may lead to a lower percent enhancement. However, we do not believe that direct quantitative comparison between these two sequences would be essentially valid because, as they represent two different GRE techniques, and due to the fact that our proposed approach is hybrid in nature and not intended to replace the gold standard Cartesian sequence in patients who are able to breath hold.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The relatively low specific organ percent enhancement compared to other studies (1,25,26) possibly reflects the hybrid nature of the final images combining data across multiple phases: pre-contrast, immediate post-injection, hepatic arterial, and early portal venous phases, which may lead to a lower percent enhancement. However, we do not believe that direct quantitative comparison between these two sequences would be essentially valid because, as they represent two different GRE techniques, and due to the fact that our proposed approach is hybrid in nature and not intended to replace the gold standard Cartesian sequence in patients who are able to breath hold.…”
Section: Discussionmentioning
confidence: 71%
“…In current magnetic resonance imaging (MRI) practice, the most commonly employed sequence in abdominal imaging for data acquisition following gadolinium administration is a breath-hold Cartesian three-dimensional gradient echo (3D-GRE) sequence (1). This sequence is often performed with parallel imaging facilitating acquisition of high quality images with average breath-hold times of 15–19 s. However, previous studies have shown that as many as 7% of patients undergoing abdominal MRI are unable to hold their breath for 15 s or more (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Gd-EOB, with just one-quarter amount of Gd per administration partially compensated for by a greater T1-relaxivity due to a higher rate of plasma protein binding (11) has a lesser total T1-shortening effect than ECCM and Gd-BOPTA in the perfused compartment. This results in a lower extrahepatic parenchymal contrast enhancement in Gd-EOB MRI than in ECCM MRI in the upper abdomen (1012,14). Nevertheless, extrahepatic evaluation of the upper abdominal organs, especially of the pancreas and lymph nodes, is routinely performed in Gd-EOB MRI of the liver and good results regarding detection and differentiation of, for example, pancreatic neoplasms including neuroendocrine tumors, have been published (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Gd-EOB achieves relatively good tissue contrasts in the extrahepatic upper abdomen during the first-pass contrast phases of dynamic liver acquisition (10). However, if the lower abdomen is intended to be included to perform a whole abdominal staging, a subsequent scan of the lower abdomen and pelvic region during the same examination would be necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation